Strategi Pengembangan Potensi Pariwisata di Kabupaten Tambrauw Provinsi Papua Barat (Tourism Potency Development Strategy in Tambrauw Regency West Papua Province) - Hasan Basri Tafalas; Leonardus R. Rengkung; Melsje Y. Memah (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2022)
The objective of this research is to identify and describe the tourism potency of Tambrauw Regency, West Papua Province and to formulate a strategy for developing tourism potential in Tambrauw Regency, West Papua Province. This research was conducted from March 2021 to November 2021. The data used in this study were primary data and secondary data. Primary data were obtained from in-depth interviews, while secondary data were obtained from the Tambrauw Regency Government, Tambrauw Regency Tourism Office and literature study. Methods of data analysis using qualitative descriptive analysis and SWOT analysis. The research results showed that, Tambrauw Regency has great tourism potential. This tourism zone is divided into two, Blue Wonder and Green Wonder. Blue Wonder is a tourism potential around the coast and Green Wonder is a tourism potential around the mountains. The results of the SWOT analysis showed that the position of developing tourism potential in Tambrauw Regency is in Quadrant I (the meeting between Strengths and Opportunities). This condition means that the tourism potential of Tambrauw Regency is in a favorable position, because it has Strengths and Opportunities that can be utilized to minimize weaknesses and be able to face various threats.